Hierarchical self-assembly of 3D lattices from polydisperse anisometric colloids - Binbin Luo (Nature Portfolio, 2019)
Anisometric colloids—which have both nanometer and micrometer dimensions—combine features of their two constituent length scales. Here, using optical microscopy and modeling, the authors find that highly polydisperse anisometric colloids self-assemble into 3D, periodic lattices in a manner hardly inaccessible to nano- or micron-scale colloids.